Influencing patterns of low-temperature nitrogen on the pore structure and oxidation characteristics of lignite - Shuliang XIE; Gang WANG; Qingdong QU; Hao LIU; Lulu SUN (Meitian dizhi yu kantan)
ObjectiveDuring fire prevention and extinguishment for mines, injecting normal-temperature nitrogen into goaves can only play an inerting role. Meanwhile, the preparation of liquid nitrogen is complicated and costly. Therefore, in the Wudong Coal Mine in Xinjiang, low-temperature gaseous nitrogen of −40 ℃ was prepared using nitrogen cooling devices and then injected into goaves to prevent the spontaneous combustion of residual coals. However, the influencing patterns of low-temperature nitrogen on the pore structures and oxidation characteristics of residual coals in goaves remain poorly understood. This tends to affect the prediction and forecast of the secondary oxidation of residual coals in goaves after low-temperature nitrogen injection ends. MethodsUsing experiments with an ultra-depth 3D digital microscope and a confocal laser scanning microscope (CLSM), nitrogen adsorption experiments, and temperature-programmed heating experiments, this study examined the surface morphologies, pore structures, and oxidation characteristic parameters of coals following sample processing using low-temperature nitrogen. Results and Conclusions After being processed using low-temperature nitrogen, the surface structures of coal samples were destroyed. With an increase in the processing time, the coal samples exhibited more developed reticular pore structures, and coal sample surfaces displayed distinct undulations. The arithmetic mean height of various points on the surfaces gradually increased from 9.562 1 μm to 21.904 5 μm, with an increase of 1.29 times. Concurrently, the average height difference of all undulations rose from 81.321 0 μm to 193.146 5 μm, representing an increase of 1.36 times. Low-temperature nitrogen primarily affected the distribution of micropores and mesopores in the coal samples, especially 2-4 nm mesopores. With an increase in the sample processing time, micropores in the samples trended upward and then downward, while mesopores therein showed an opposite trend. As a result, the total pore volume increased by 0.004 3 cm3/g, with the 2-10 nm mesopores identified as the largest contributor, and the specific surface area of coal samples determined using the Brunauer–Emmett–Teller (BET) theory increased by 0.049 3 m2/g. After sample processing using low-temperature nitrogen, the CO production, heat release intensity, and oxygen consumption rates significantly increased during coal sample oxidation. Notably, their increments increased with the sample processing time. Specifically, the CO production, oxygen consumption rate, and maximum heat release intensity increased by 5.02×104 μL/L at maximum, 2.33×10−8 mol/(cm3·s), and 2.25×10−2 J/(cm3·s), respectively. Additionally, the characteristic temperature of oxidation reactions in the coal samples decreased. The results of this study reveal that low-temperature nitrogen can destroy the pore structures of coals and enhance their oxidation performance. In the case where low-temperature nitrogen of −40 ℃ is injected into a goaf, its macroscopic dominant effect of inerting and cooling can effectively suppress the spontaneous combustion of coals. When oxygen is restored after nitrogen injection ends, coals show a higher tendency for spontaneous combustion after being treated due to the microscopic side effect of low-temperature nitrogen, enhancing the secondary oxidation intensity.